The process of turning a “green” renewable energy into “non-green” for the local people: an observation-based study from Southern Chile - Rana, Md. Sohel (Latin American Journal of Energy Research, 2021)
This paper describes an observation-driven research journey to explore the process of how a so-called “green” renewable energy technology could turn into “non-green” for the local communities. The study is conducted in Southern Chile that has been receiving a number of hydroelectricity-based renewable energy projects in recent years and most of those projects have been receiving strong social resistance from the local communities. Qualitative methods are availed in the study to explore local realities about the community people’s attitude and action-building towards these projects. The research results that a “green” project could be “economically green” to the local people who are concerned of their individual lives and livelihoods, however, “less green” to the group of community people emotionally attached to their lands and territory-based culture.
Keywords: emotional attachment, green technology, hydroelectricity, local knowledge, trust.